Gaya Bahasa dan Teknik Persuasif dalam Iklan Makanan Daring Izakaya Jepang - Anwar, Aulia Arifbillah; Dewi, Citra; Nugraha, Gilang Ramadhan (Departemen Sastra Jepang, Fakultas Ilmu Budaya, Universitas Hasanuddin, 2024)
The structure of advertisements consists of language, images, and motion that contain words with emotions and form imagination, thus influencing the readers and listeners to act as expected by the advertisers. The diction and language style used in their food promotion advertisements is very diverse and attractive due to the persuasive effect on readers and potential consumers. The purpose of this research is to determine the stylistic elements, namely language style and persuasive technique found in the online advertisements of Izakaya (Japanese-style bar) with data sources taken from three Izakaya companies: Torikizoku, Ikkyu, and Hananomai in Tokyo, Japan. The theory used is the theory of language style and persuasive language function by Gorys Keraf. In conducting this research, the author uses a qualitative method. The analysis technique uses the literature study method. Data is obtained by documenting food advertisements on the official websites of Izakaya Torikizoku, Ikkyu, and Hananomai in Tokyo. From the analysis results, 9 data containing the language style of hyperbole identified in words or phrases such as